Role of intravenous amino acid infusion in cases of oligohydramnios and its effect on amniotic fluid index and fetal weight gain - Shree, Pragya; Mittal, Nupur; Kanti, Vaibhav; Vishwakarma, Sonia (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Oligohydramnios in early pregnancy is attended by serious consequences to the fetus. Various conditions associated with oligohydramnios increase perinatal mortality and morbidity. Different medical and interventional methods have been tried to treat oligohydramnios. The present study was done to study the effect of intravenous amino acid infusion on amniotic fluid index (A.F.I) and fetal weight gain. Methods: A total of 100 patients of oligohydramnios were studied. They were divided equally into study group and control group of 50 patients each by random allocation. The patients in the study group were given intravenous infusion of 200 ml of amino acid on alternate day for one week while those in the control group were not given any intervention. Both the groups were monitored for change in A.F.I and fetal weight gain by ultrasound at the end of the week. Results: The average gain in A.F.I in the study group (2.57 ± 0.68 cm) was more than in the control group (2.13 ± 0.84 cm). The average gain in fetal weight in the study group was 150.0 grams with SD of ± 37.8 grams while in the control group it was 82.14 grams with SD of ± 67.1 grams. Conclusions: Thus intravenous infusion of amino acids increases short term A.F.I and also improves fetal weight and thus has a beneficial effect to both mother and fetus in case of oligohydramnios in developing countries. However, larger studies with controlled trial are needed to be done.